Studies on Optical, Thermal and Mechanical Properties of Glasses for Automotive Applications - Kumar, Santosh (Thapar Institute of Engineering and Technology, Patiala, 2025)
The research problem in the present thesis is related to improve the properties of automobile windshield glasses and to explore the recyclability of these glasses to reduce the carbon footprint. To achieve these objectives, first the study has been conducted on the commercial available automobile windshield glasses of different cars. Based on the initial findings, a series of silicate-based samples are synthesised using the melt-quench technique. The physical, structural, optical, thermal and mechanical properties of the prepared glasses are studied using various experimental techniques to determine their suitability as automobile windshield glasses. Based on the above properties, the windshields with better optical and mechanical properties are used for recycling and reusability by adding a small quantity of glass formers and fining agents, such as B2O3, P2O5, NaCl, and KCl. The present thesis contains five chapters followed by the references. Chapter 1 deals with the basics of oxide glass, followed by the required properties for windshield glass in vehicles and the methods with which these properties are adapted for automotive applications. Furthermore, this chapter describes the types of glass used in automotive applications, their required properties, and the role of different structural units, their amounts and constituents in silicate-based glasses used in automobiles. Chapter 2 is associated with the comprehensive review of the literature on silicate-containing alkali and alkaline earth oxide glasses for automotive applications, particularly windshield glasses, which highlights their critical role in enhancing the mechanical, thermal, and optical properties of automotive glasses. Alkali, alkaline, and intermediate oxides influence the optical properties of the glasses, such as transparency and refractive index, along with other properties also. The presence of these oxides usually reduces the melting temperatures of the glass composition and allows for high optical clarity, which is critical for vehicle windshield glass. Based on this literature review, the motivation of the present study, along with the objectives of the thesis are outlined at the end of this chapter. Chapter 3 gives the details of the glass synthesis, their characterisation and testing using various experimental techniques. The melt-quench method is employed to prepare the samples using conventional chemicals in powder form. X-ray diffraction (XRD) is used to identify the nature of the as-prepared glasses, while Fourier transform infrared (FTIR) and Raman spectroscopy are used to study the local structural units with respect to wave numbers and compositions. The softening and characteristic temperatures are analysed using a dilatometer and differential scanning calorimetry (DSC), respectively, to confirm the thermal expansion and glassy nature of the synthesised samples. The elements present in commercially available windshield glasses are analysed using energy-dispersive spectroscopy (EDS). The elemental composition and oxidation states of the ions in the samples are also examined through X-ray photoelectron spectroscopy (XPS) on selected glasses. Optical and mechanical properties are investigated using diffuse reflectance spectroscopy (DRS) and a Vickers microhardness tester, respectively. Chapter 4 describes the results and discussion of the prepared samples. In this chapter, interpretations of the data obtained from various characterisation techniques have been discussed in detail. This chapter is further divided into five sub-sections. The first section represents the properties of commercially available windshield glasses. XRD confirms the amorphous nature of the windshield glass of various cars. The chemical composition of available windshield glasses exhibits some variations in their glass composition. Audi A6 Sedan (A6) shows the highest optical band gap (Eg) (3.66 eV), whereas BMW 7 Sedan (B7) shows the lowest Eg (3.40 eV). The highest transparency, hardness, and fracture toughness are observed for the BMW 7 Sedan compared to other windshield glasses due to the moderate contents of Al2O3 in its composition. The Al2O3 and K2O plays a very important role in polymerisation and influence the optical and mechanical properties of windshield glasses. Thus, the small variations in Al2O3 and K2O in glass compositions lead to an increase in the transparency and mechanical properties as well as prevent devitrification of these glasses. In the second section, the properties of 64SiO2−16Na2O−12CaO−2Al2O3−(6−x)MgO− (x)Li2O; (x = 0, 2, 4, and 6 mol%) system have been explained. XRD patterns confirm the amorphous nature of the as-prepared glasses. FTIR and Raman spectra indicate that the addition of Li2O instead of MgO changes the NBOs formation in asymmetric ways, such as enrichment in Q3 and Q1 silicate structural units in place of Q2. The Eg decreases from 4.03 to 3.88 eV while the Urbach energy (Eu) increases (0.31-0.43 eV) with the addition of Li2O content in place of MgO. The optical and mechanical properties decrease with the concentration of Li2O in the glasses due to the decrease in the structural unit connectivity. The third section describes the properties of 64SiO2 − 16Na2O − 12CaO − 2Al2O3 − (6 − x)MgO−(x)K2O; (x = 2, 4, and 6 mol%) systems. The density and oxygen packing density decrease with the addition of K2O in place of MgO in the glasses. XRD patterns confirm the shift in the broad halo between 20◦ to 30◦ with the increase in K2O content. The FTIR and Raman spectra confirm the presence of Q1, Q2, and Q3 units of silicate in the glasses. K2O addition increases the number of NBOs and the Urbach energy, as well as the transparency of the glasses. On the other hand, the Eg decreases with increasing K2O concentration because of the increase in ionicity in the glasses. The microhardness and fracture toughness decreased due to the variation of the field strength of K+ and Mg2+ cations. The fourth section describes the properties of (64−x)SiO2−(x)B2O3−16Na2O−12CaO− 2Al2O3 −6MgO; (x = 2, 4, and 6 mol%) systems. Adding B2O3 in place of SiO2 in glasses shows a strong effect on optical and mechanical properties. The B2O3 content decreases the density as well as the glass network volume. FTIR spectra show that, with the addition of B2O3, the Q3 silicate structural units are dominating. The B2O3 content increases the hardness of the glasses. The maximum hardness is observed for 6 mol% of B2O3 content glass, i.e., 6.93 GPa. The 62S-2B sample has higher values of optical basicity, band gap, and oxide ion polarisability, which is due to the presence of a higher number of NBOs in this glass. The 52S-6B glass has the highest hardness and fracture toughness, which can be attributed to the high bond strength of the B-O than the Si-O bond. The highest transparency is 88% for 62S-2B glass. The fifth section deals with the recycling of the BMW 7 Series Sedan windshield to study their feasibility for reuse in automobiles. All the recycled glasses are formed without any tendency of phase separation in glasses. With the addition of glass formers (B2O3 and P2O5) and fining agents (NaCl and KCl), the tendency to diffuse alumina from a recrystallised alumina crucible increases. The RB7 glass has the highest Eg, i.e., 3.54 eV instead of the RB7B sample (3.43 eV). The RB7B and RB7P have the highest (2.25) refractive index, which suggests that the maximum number of NBOs are formed in these glasses as compared to other samples. The additives (B2O3, NaCl and KCl) decrease the hardness from 5.27 to 4.29 GPa while the fracture toughness increases from 0.54 to 0.63 MPa m1/2 of the recycled glass. Interestingly, the RB7P shows better properties than the other recycled glasses. The presence of Al2O3 and P2O5 was found to significantly influence the polymerisation process and thereby impact the optical as well as mechanical properties of the recycled glasses. Chapter 5 describes the overall conclusion drawn from the physical, structural, optical, thermal, and mechanical properties of the prepared samples. To enrich this work, the future scope of the present study has also been given at the end of this chapter. Overall, 20 glasses are prepared and characterised. The highest transparency, along with mechanical properties and other properties, is observed in the SML-0, SML-6, 58S-6B and RB7 glasses. The recycled glasses RB7 is usable without compromising the transparency and other properties. This approach not only paves the way to decrease the carbon footprint but also increases the circular economy. At last, the future scope of the work is proposed to explore more recycling of the windshield glasses with different additives, such as TiO2/Cr2O3.
Keywords: Silicate glass; Windshield; Recycled; Automotive applications; Transparency; Hardness